TRANSLATION OF POLITICAL ADVERTISEMENTS FROM ALAS LANGUAGE INTO INDONESIAN - Saddam Hasrul; Tasnim Lubis; Achdial Farhan Abus (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
The objectives of this study are to describe the process of translation of political advertisements from Alas language into Indonesian, to describe the problems of translating political advertisements from Alas language into Indonesian and to describe how the language style of Alas language in political advertisement persuaded the voters. The qualitative research was applied. The data were collected by using camera and text in the banners or pamphlets were rewritten on paper. There are seven data of political advertisement that used Alas language in election of year 2019. The writer translated the political advertisement from Alas language into Indonesian by using Newmark procedure. The data were analyzed by using Larson’s Steps in a Translation Project that consists of: establishing the project, revised draft, consultation and final draft by attached the picture of the political advertisement in Alas language. The findings are: first, translation political advertisement from Alas language into Indonesian deliberated morphology, cultural equivalent, and descriptive equivalent. Second, it used intimate style. Third, there are some similarities word in Alas language and Indonesian. Fourth, language style in political advertisement in Alas language used proverb and euphemism. As a result, translation political advertisement from Alas language into Indonesian concern to cultural equivalent that the problems in translating political advertisement from Alas language into Indonesian related to the culture that covered explicit and implicit meaning and language style of political advertisement of Alas language used intimate style through proverb and euphemism.